Practical skills and safety requirements in the profession of pyrotechnician - Cioara Cristian Raul; Tuhuț Ligia Ioana; Manea Florin (MATEC Web of Conferences, 2024)
National legislation states that a pyrotechnician is a person who has specialist knowledge and is authorized to handle and use pyrotechnic entertainment items. It is necessary to acquire technical and practical knowledge, but above all the training of skills in the proper use of pyrotechnic articles, taking into account the specific risk and the complexity of the execution of the operations. At INCD INSEMEX Petro.ani, the technical and practical facilities for the organization of qualification courses in the profession of pyrotechnician have been developed, leading to an increase in the level of knowledge and the acquisition of practical skills. In this sense, the infrastructure for teaching and verifying the appropriate acquisition of the disseminated information was developed based on the application of modern pedagogical and psychopedagogical concepts to facilitate the learning process for people who come from a heterogeneous environment from the perspective of age differences and level of studies/ accumulated experience held. The paper highlights the results of the modernization of the methodological and practical infrastructure as well as the technical facilities in terms of optimizing and increasing the quality of the training process for the pyrotechnician qualification.